Efeito do tratamento com Ginkgo biloba sobre a inflamação hipotalâmica presente em ratos com obesidade induzida pela dieta - Julio, Viviane da Silva [UNIFESP] (2015)
It has been described that treatment with the standardized extract of Ginkgo biloba (EGb) promotes improvement of inflammatory conditions and this effect arises through inhibition of the Toll-like receptors. It is known that elevated circulating levels of saturated fatty acids that activates inflammatory pathway through the Toll-like receptor 4, promoting the expression of proinflammatory cytokines involved in obesity, such as hypothalamic inflammation. Therefore, the aim of this study was to analyze the effect of EGb on pathways of Toll-like receptor 4, serotonergic and hypothalamic neuropeptides of diet induced obesity (DIO) rats. The results showed no effect of EGb on the approaches. However, we observed in the EGb treated group a reduction in cumulative food consumption trend and a significant reduction in the total body weight gain over the period of treatment and in the mass of the retroperitoneal fat depot. Furthermore, the 5-HT1B levels and AgRP gene expression showed a decreasing trend in rats treated with EGb, these data could explain at least in part the reduced food intake observed in this study. The results regarding the reduction of body weight and visceral fat mass in obese animals, even maintaining high fat and high calorie diet during the herbal treatment, allow us to suggest that EGb represent an alternative therapy to prevent and / or treat obese people who have difficulties in getting used to a healthy diet and physical exercise. Therefore, it is necessary to elucidate the mechanisms of action of this herbal medicine on energy homeostasis.